Competition policy and law - Williams, M (Foundation for Law, Justice and Society, 2007)
Competition policy and law, appropriately implemented and enforced, are essential to the optimal functioning of a market-orientated economy. International organizations, including the World Bank, the Organization for Economic Cooperation and Development (OECD) and regional groupings such as the European Union (EU), the Association of South East Asian Nations (ASEAN) and Asia-Pacific Economic Cooperation (APEC), all emphasize, to a greater or lesser extent, the need for a pro-competition policy to be adopted, to promote industrial efficiency and economic growth. The unspoken, but implicit, precondition for an effective competition policy is that the national government is ideologically committed to markets as the primary economic regulator, rather than to state-centred planning, or excessive public sector intervention to promote ‘national champions’. For markets to function, there must be competition. The intriguing question is whether the Chinese authorities now accept this ideological position, and the need for a competition law to enhance domestic competition, after almost 30 years of economic reform. This brief will go on to explore the validity of the assertion that the adoption of a Chinese competition law, in present conditions, may be inappropriate, and might, in fact, impede the creation of a more economically efficient market.